Efektivitas Penggunaan Metode Pembelajaran Diskusi Tipe Buzz Group Terhadap Keaktifan Belajar Peserta Didik - Mas Sa’id, Putra Ananda; Syar, Nur Inayah; Sulistyowati (UNIVERSITAS SERAMBI MEKKAH, 2024)
This research aims to: (1) describe the implementation of the Buzz Group teaching methodology in mathematics classes; (2) assess the effectiveness of the Buzz Group teaching methodology in terms of student learning activities; and (3) assess the impact of the Buzz Group teaching methodology on student learning activities in mathematics classes. This penetration method is quantitative and uses a pre-experimental approach. The research population was all level IV students of MIS Miftahul Huda 2 Palangka Raya who were divided into three classes. Purposive sampling is a sample preparation technique based on predetermined criteria. The data collection technique used in this research is an observation sheet for data collected during the continuous learning process and data collection on student behavior during learning. The research results show that: (1) the Buzz Group teaching method is applied to homework material with a ratio of 3 to 73 with appropriate criteria. The effectiveness of using the Buzz Group teaching methodology has been proven with an effect size of 3.248. The influence of the Buzz Group learning method on the learning activities of class IV-B students at MIS Miftahul Huda 2 Palangka Raya was studied using a paired sample of T Tests which showed a significant difference (0.000 < 0.05) with an average of around 10.307 indicating a significant influence. after using the Buzz Group learning method.